BORROWED NEOLOGISMS IN ARABIC LANGUAGE AND THEIR ADAPTATION - Abidin З А (Journal of Oriental Studies, 2016)
With the development of science, the pervasion of new technologies in daily life and the expansion of multilateral relations with other people and cultures, new concepts and titles appear in the language. Vocabulary of modern Arabic, like every other language, is updated with new foreign words - neologisms. This phenomenon takes place in everyday life, in the media and in the Arab scientific terminology. This article reviews the lexical borrowings and neologisms in Arabic language also their degrees of adaptation and assimilation